Treatment of refractory subacute cuataneous lupus erythematosus with baricitinib. (13th December 2021) - Joos, L.; Vetterli, F.; Jaeger, T.; Cozzio, A.; von Kempis, J.; Rubbert‐Roth, A.
Abstract : We report on a patient who presented with refractory subacute cutaneous lupus erythematosus. The scaly annular and polycyclic patches/plaques, and hyperkeratotic lesions on multiple fingers improved rapidly after treatment with baricitinib.